Carbon Nanotube-Modified MnO2: An Efficient Electrocatalyst for Oxygen Reduction Reaction - Woon, Chee Wai; Islam, M. Amirul; Ethiraj, Baranitharan; Huei, Ruey Ong; Cheng, C. K.; Chong, Kwok Feng; Hegde, Gurumurthy; Khan, Maksudur R. (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
In this work, manganese dioxide/carbon nanotube (MnO2/CNT) have been synthesized by sonochemical-coprecipitation method and demonstrated that it could be an effective electrocatalyst for oxygen reduction reaction (ORR). Moreover, the effect of CNT inclusion with MnO2 was also investigated for ORR. The physical and electrochemical properties of the MnO2/CNT were examined by powder X-ray diffraction (XRD), Fourier Transform Infrared (FT-IR) spectroscopy, Brunauer-Emmett-Teller (BET), Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy/Energy Dispersive X-ray (FESEM/EDX), Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS), Mott-Schottky and Rotating Disk Electrode (RDE) analysis. CV showed higher currents for the ORR in MnO2/CNT than CNT; however, ORR current dropped when the MnO2 loading was increased from 20–40 %. The EIS analysis showed that charge-transfer resistance for MnO2/CNT was significantly lower compared to the MnO2 indicating that MnO2 has good contact with CNT and the composite possess high electrical conductivity. Mott-Schottky results demonstrated that incorporation of CNT into MnO2 resulted in producing larger electron density in n-type MnO2/CNT compared to MnO2 which is liable for efficient electron donation from the Mn3+ to adsorbed oxygen in the rate determining step. RDE results showed that MnO2/CNT follows 4e− transfer pathway, indicating its ability to act as an effective ORR electrocatalyst.